EFFECTS OF SPECIFIC TRAINING MODELS ON QUADRICEPS AND HAMSTRING - Sandra Vujkov; Tatjana Trivić; Patrik Drid (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2008)
This reaserch included 30 participants. Examinees were divided in three subsamples. First subsample included 10 soccer players (22,0±2,82 years 79,3±8,23 weight), second subsample included 10 judokas (19,6±2,63 years 82,7±19,42 weight) and third subsample was made of 10 students that were not involved in any sport (21,1±0,57years 79,1±11,17 weight). By applying t-test conclusions we remade. Between judokas and soccer players there were no statistically significant differences found in analyzed variables. Between judokas and students were found visible differences in all analyzed variables in favour of judokas ( significance p=0,01 particularly in variables PTHR and PTHL). Between soccer players and students significant difference (p=0,05) were found in variables PTQL and PTQL/W in favour of soccer players.